Pengaruh Agresivitas Pelaporan Keuangan terhadap Agresivitas Pajak dengan Mekanisme Good Corporate Governance sebagai Pemoderasi - Krismonika, Mahasani Puspitarani; Tartila, Nilda (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Companies are currently involved in various forms of tax planning to reduce the estimated tax liability. On the other hand, aggressive tax actions are bad for the companies because it requires them to report lower profits. Frank et al (2009) found there was a tendency that companies were able to report greater profits and have a low tax burden simultaneously. Thus, it can be said that trade-offs don't always occur. This study aims to assess the influence of the aggressiveness of financial reporting on tax aggressiveness in manufacturing companies from 2015-2018 by using the mechanism of Good Corporate Governance as a moderating variable. The data used in this study are secondary data obtained from the financial statements and annual reports of manufacturing companies from the Indonesia Stock Exchange. The population of this research is 27 manufacturing companies listed on the Indonesia Stock Exchange. Selection of the sample was done using the purposive sampling method. The analytical method used in this research is multiple regression or multiple regression with the SPSS version 25 computer program. Hypothesis test was performed using multiple regression methods and MRA (Moderated Regression Analysis). The results of this study indicate that the aggressiveness of financial reporting on manufacturing companies simultaneously has a significant positive effect on tax aggressiveness with a significance value of 0.003. The mechanism of Good Corporate Governance with indicators of Institutional Ownership and Managerial Ownership simultaneously has a significant negative effect on tax aggressiveness with a significance value of 0.001 and 0.007. As well as the mechanism of Good Corporate Governance, it is stated that it can weaken the effect of the aggressiveness of financial reporting on tax aggressiveness. Key words : Financial Reporting Agressiveness, Tax Aggressiveness, and Good Corporate Governance